A STUDY ON MAIN CHARACTER’S OBSESSION IN “PERFUME: THE STORY OF A MURDERER” NOVEL BY PATRICK SUSKIND - Zamroni, Mohammad; Diansyah, Mohammad Rival; Nirbowo, Mesakh Januarta (JURNAL LITERASI, 2023)
The study is intended to enrich the knowledge of literature and literary works as the product, especially in Novel genre. The aims on this study research are to find out the main character’s obsession in the Perfume: The story of a murderer’s novel, and explained what is the impact of his obsession that brings him to the tragic life. The qualitative descriptive is used to apply the data collection method, the data are from the text of the novel by Patrick Suskind entitle Perfume: The story of A Murderer. After learn and analyze the data, the researcher knows that, Perfume: the story of a murderer has the main character his name is Grenuelle, and he has the big obsession to be the famous perfume creator, but it was giving impact to his life. So the researcher can analyze the story, and conclude that the obsession of the main character gives impact for his life, and bring him to the tragic life.